2019
DOI: 10.4314/njt.v38i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Model for predicting mix formulation in the production of insulating refractory bricks using Nigerian fire-clays and coconut shell

Abstract: Lack of appropriate mix formulation has the tendency to degrade the strength of refractory bricks. This paper presents a model developed for evaluation and prediction of mix formulation for production of insulating refractory using Osiele and Ukpor fireclays blended with coconut shell particulates. The chemical compositions of the raw materials were analysed. The samples were prepared by mixing the clays and coconut shell of grain sizes 212 -600µm. Then air and oven dried for 24 hours at room temperature and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 4 publications
3
3
0
Order By: Relevance
“…The highest and lowest apparent porosities were 89.3 and 56.8% for samples C 4 and C 3 with Clay/L-C ratios of 4:1 and 3:2, respectively. There is also an agreement with the investigation done by Obidiegwu et al 29 that increased kaolin clay content resulted in reduced porosity values; as seen in Figure 2 (Table 3).…”
Section: Chemical Compositionsupporting
confidence: 92%
See 1 more Smart Citation
“…The highest and lowest apparent porosities were 89.3 and 56.8% for samples C 4 and C 3 with Clay/L-C ratios of 4:1 and 3:2, respectively. There is also an agreement with the investigation done by Obidiegwu et al 29 that increased kaolin clay content resulted in reduced porosity values; as seen in Figure 2 (Table 3).…”
Section: Chemical Compositionsupporting
confidence: 92%
“…The result agrees with previous studies where increased bio-based fibers content lowered thermal conductivity. 3,28,29 This value is also comparable with the thermal conductivity value of ceramic foam insulation material.…”
Section: Resultssupporting
confidence: 68%
“…The effect of adding any combustible material, like saw dust and polystyrene is to increase the porosity and consequently decrease the bulk density and crushing strength. This effect has long been reported by several authors [4,10,11,14]. An interesting result was obtained when the values of fractional porosity (𝑝) were correlated to those of strength (𝜎).…”
Section: Effect Of Pore Generating Materialssupporting
confidence: 56%
“…The same authors later presented a comprehensive review on the matter that reported the use of vegetable waste in the preparation of different ceramic products including insulating refractories [13]. Using gmelina seed shells as porosity promoter, Obidiegwu et al [14] prepared insulating refractory samples on firing at temperatures reaching 1050 o C. However, their results were short of producing sound bricks since the minimum bulk density reached was 1.5 g.cm -3 corresponding to a compressive strength of 0.126 MPa. Also, the bricks prepared by Isinkaye et al [15] by firing at 1200 o C using rice husk possessed high bulk densities (0.95 -1.6 g.cm -3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the samples with more than 20% composition of sawdust collapsed at higher temperatures. Obidiegwu et al, (2020) evaluated the thermal and mechanical behaviour of porous refractory bricks made from local fire-clay combined with the particulates of the shells of gmelina seeds. The results from the research revealed that, bricks containing 25 to 30 wt% of shells of Gmelina seeds acquired the recommended thermal conductivity (0.12 -0.28 W/mK) and crushing strength more than 1000 kN/m 2 which is the standard range recommended by ASTM.…”
Section: Introductionmentioning
confidence: 99%